ANÁLISIS CUANTITATIVO DE LA TELEVISIÓN Y EL VÍDEO EN INTERNET (WEBTV). ESTUDIO DE FORMATOS, CONTENIDOS Y ORIGEN - José Borja ARJONA MARTÍN,Juan Salvador VICTORIA MAS (Fonseca, Journal of Communication, 2023)
Due to the significant increase in the last five years of audiovisual content distribution over the web, this paper is focused on a study aimed at the description and classification of a wide sample of audiovisual initiatives whose access is carried out by means of the World Wide Web. The purpose of this study is to promote the debate concerning the different names of these incipient.